Childhood Urinary Tract Infection: Clinical and Laboratory Profiles and Antimicrobial Sensitivity Patterns - Das, Ashith Chandra; Azad, Md Tarek; Chowdhury, Jannatul Ferdush; Saha, Priyanka; Akter, Farida; Talukder, Aloka Nanda (Delta Medical College Journal, 2025)
Background: In infants and children, urinary tract infection (UTI) is a serious bacterial infection. Early detection and treatment can reduce the risk of substantial morbidity. Objective: The objective of the study was to evaluate the clinical profile, laboratory findings and antimicrobial sensitivity pattern of uropathogens causing urinary tract infection in children. Materials and method: This cross sectional study was conducted in the Department of Paediatrics Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, Bangladesh, from 1st January 2019 to 31st December 2019. A total of 150 cases aged 2 months to 12 years were enrolled in the study by consecutive sampling method. Results: Among 150 cases, 60% were female with a male-female ratio of 1:1.5. Overall, the highest number of cases were within the age group of 1 to <5 years (52.7%). Fever (74%) was the most common presenting feature, followed by abdominal pain (45.3%), dysuria (43.3%), increased frequency of micturition (33.3%), and nausea and vomiting (30.3%). Significant pyuria was present in 61.3% of cases, and microscopic haematuria was in 24% of cases. Urine culture was positive in 60% of cases. Escherichia coli (57.9%) were the most common isolated organism, followed by Klebsiella (33.3%). The most of the organisms were highly sensitive to imipenem (87.8%), nitrofurantoin (74.4%), amikacin (61.1%) and levofloxacin (48.9%). Conclusion: Children under five and those who were female had higher rates of UTI. Judicial use of antibiotics is necessary to treat these children. Delta Med Col J. Jul 2022;10(2): 52-58